The idea of `Mangilik el`: Turkic outlook and civiliazation - Ешметовa Б. Б. (Journal of Oriental Studies, 2018)
In this article the role of idea “Mangilik el” in Turkic outlook as an indicator of an Old Turkic civilization is considered. Also, the purposes and the directions of the main ideas in the course of formation of the state are analyzed. The characteristic is given to the concept “Mangilik el” of a language picture of the world of a Turkic civilization and outlook. Scientific opinions and views of leading experts concerning this subject are presented.